Statistical optimization for greener synthesis of multi-efficient silver nanoparticles from the Hypocrea lixii GGRK4 culture filtrate and their ecofriendly applications - Gupta, Guddu Kumar; Koli, Devesh; Kapoor, Rajeev Kumar (Frontiers in Nanotechnology, 2024)
The culture filtrate of Hypocrea lixii GGRK4 played a vital role as a reducing and stabilizing agent in the myco-synthesis of AgNPs using silver nitrate (AgNO3). The extracellular extract derived from fungi emerged as a noteworthy option for synthesizing silver nanoparticles (AgNPs) due to its potential composition of metabolites, including enzymes and other bioactive substances. Hence, the presence of a dark brown colour serves as a key indicator for the biosynthesis of AgNPs through the reduction of Ag (I) ions to Ag by the fungal culture filtrate. To facilitate the synthesis of AgNPs, a combination of hybrid technologies, specifically the "one factor at a time" approach and statistical tools such as Response Surface Methodology, was employed using a face-cantered central composite design (FCCCD). Utilizing a modified CX medium with a pH of 5.02 supported the fungi synthesising AgNPs at a temperature of 30℃. The multiefficient AgNPs were characterized through various techniques, including UV-visible Spectrophotometry, zeta size and potential analysis using a Zeta size analyser, Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and fluorescence spectroscopy. The biosynthesized AgNPs have significant associated functional groups revealed by FTIR analysis. TEM histogram analysis shows these multiefficient AgNPs have a size of 17.34 nm. Similarly, it has 450 nm and 390 nm of emission and excitation spectra, revealed by fluorescence spectra analysis. Compared to standard, the biosynthesized AgNPs have significant antibacterial, free radical scavenging properties and dye degradation capability. Additionally, the half-maximal inhibitory concentration (IC50) value was found statistically significant based on t-test analysis. Finally, the biosynthesized AgNPs could be used in potential applications encompassing eco-friendly degradation, antimicrobial activity, and therapeutic applications such as free radical scavenging properties.